Tricin Biosynthesis and Bioengineering - Lam, Pui Ying; Lui, Andy C. W.; Wang, Lanxiang; Liu, Hongjia; Umezawa, Toshiaki; Tobimatsu, Yuki; Lo, Clive (Frontiers in Plant Science, 2021)
Tricin (3ʹ,5ʹ-dimethoxyflavone) is a specialized metabolite which not only confers stress tolerance and involves in defence responses in plants but also represents a promising nutraceutical. Tricin-type metabolites are widely present as soluble tricin O-glycosides and tricin-oligolignols in all grass species examined, but only show patchy occurrences in unrelated lineages in dicots. More strikingly, tricin is a lignin monomer in grasses and several other angiosperm species, representing one of the “non-monolignol” lignin monomers identified in nature. The unique biological functions of tricin especially as a lignin monomer have driven the identification and characterization of tricin biosynthetic enzymes in the past decade. This review summarizes the current understanding of tricin biosynthetic pathway in grasses and tricin-accumulating dicots. The characterized and potential enzymes involved in tricin biosynthesis are highlighted along with discussion on the debatable and uncharacterized steps. Finally, current developments of bioengineering on manipulating tricin biosynthesis towards the generation of functional food as well as modifications of lignin for improving biorefinery applications are summarized.